2022
DOI: 10.4490/algae.2022.37.5.29
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of the economic seaweeds <italic>Chondrus</italic> (Gigartinales, Rhodophyta) in the northwest Pacific based on <italic>rbc</italic>L and COI-5P genes

Abstract: The red algal genus Chondrus have long been used as raw materials for carrageenan and dietary fiber in health foods. Despite the importance of genetic information in safeguarding natural seaweed resources, knowledge of the population genetics of Chondrus in the northwest Pacific is limited. In this study, genetic diversity and phylogeographic structure of 45 populations (777 specimens) of Chondrus from Korea, China, and Japan were evaluated based on mitochondrial COI- 5P gene sequences, and phylogenetic relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…Low genetic differentiation, as observed in both Plocamium species in this study, has also been observed in other marine macroalgae in the NW Pacific: Pachymeniopsis elliptica / P. lanceolata (Yang et al 2021b), Chondrus ocellatus / C. nipponicus (Yang and Kim 2022), and Gratelopia asiatica / G. jejuensis (Yang et al 2021c). The absence of distinct geographic genetic structures reflects an apparent lack of major oceanographic barriers in Korea.…”
Section: Supplementary Materialssupporting
confidence: 83%
“…Low genetic differentiation, as observed in both Plocamium species in this study, has also been observed in other marine macroalgae in the NW Pacific: Pachymeniopsis elliptica / P. lanceolata (Yang et al 2021b), Chondrus ocellatus / C. nipponicus (Yang and Kim 2022), and Gratelopia asiatica / G. jejuensis (Yang et al 2021c). The absence of distinct geographic genetic structures reflects an apparent lack of major oceanographic barriers in Korea.…”
Section: Supplementary Materialssupporting
confidence: 83%
“…The gene flow by ocean currents was also shown in the distribution of haplotype H04, which occurred from Nanji Island to the coasts of Korea and Dailan (Figure 5). The occurrence of H04 in the entire coast of Korea may be the result of high gene flow between the Korean populations due to complex oceanic currents, which has also been observed in red algal species of the genus Chondrus Stackhouse (Yang and Kim, 2022). The influence of ocean currents affects population distribution may be confirmed in future studies including populations along the coasts where the Tsushima Warm Current passes.…”
Section: Discussionmentioning
confidence: 76%
“…We found that COI-5P sequences from M. pilulaora showed relatively lower haplotype diversity (Hd = 0.547) than COI-5P sequences from other red macroalgae in the northwest Pacific (Hd = 0.809 in Plocamium luculentum [Yang and Kim 2023]; Hd = 0.665 in Gracilaria vermiculophylla [Zhong et al 2020]; Hd = 0.626 in Chondrus ocellatus [Yang and Kim 2022]; Hd = 0.530 in Chondrus nipponicus [Yang and Kim 2022]). Interestingly, the pattern of the haplotype network of M. pilulaora was similar to that of other red macroalgae in Korea, which showed one or two prevailing haplotypes distributed widely, and several haplotypes derived from the prevailing haplotypes (Yang et al 2021a, b;Yang and Kim 2022). This low haplotype diversity may render populations of this species vulnerable to environmental alterations caused by global climate change (Pauls et al 2013).…”
Section: Discussionmentioning
confidence: 76%